Woody community dynamics of a gallery forest in the transition Cerrado-Amazon Forest in Eastern Mato Grosso, over a seven year period (1999 to 2006) - Miguel, Aline; Marimon, Beatriz Schwantes; Oliveira, Edmar Almeida de; Maracahipes, Leandro; Marimon-Junior, Ben Hur (Biota Neotropica, 2011)
The study was carried out on the gallery forest of the Bacaba stream (14º 43' 12.2" S and 52º 21' 36.7" W), in the transition between Cerrado and Amazon Forest in Nova Xavantina, Mato Grosso State, Brazil. The objective was to evaluate and compare the dynamics of the woody community at three sections of the forest (upper, middle and lower) in a topographic gradient over a seven year period. The inventory consisted of 141 permanent plots (10 × 10 m) distributed in the three sections where all individuals > 15 cm girth at breast height were recorded in 1999 and 2006. Based in density and basal area, the Periodic Annual Increment (PAI) and dynamics parameters were calculated. In all forest sections the mortality was higher than recruitment. The lower section was the most dynamic, because presented the higher mortality (6.84%) and recruitment (4.73%) rates. The community was dynamic, probably due to its current intermediary successional stage and the different environmental conditions depending on the topography. The PAI values of the species in common with all sections confirm differences in increment, indicating that some have restrictions and others benefit to grow in certain environments. On the other hand, some species had similar PAI values in the three forest sections, confirming a plasticity to adapt to different environmental conditions. The species presented different recruitment, mortality and increment rates, related to the ecological groups and topographic position. We suggest that the topographic gradient and seasonal flooding contribute to include this community among the most dynamic tropical forests.